Management of multiple herbicide resistant little seed canary grass (Phalaris minor Retz.) in wheat - Puneet Kumar Chhokar; Umesha C.; Ankur Chaudhary; Kailash Prajapat (Annals of Agricultural Research, 2025)
Little seed canary grass (Phalaris minor Retz.) is a major weed in many wheat-producing countries. The excessive dependence on herbicides for its control led to the evolution of multiple herbicides resistance and yield losses. The first case of resistant P. minor in India was to the Photosystem-II inhibitor isoproturon in the early 1990’s. Now P. minor has been found resistant to Acetolactate Synthase (ALS) inhibitors, Acetyl-CoA Carboxylase (ACCase) inhibitors, Photosystem II inhibitors-based post emergence herbicides in northern Indian plains. It is highly competitive and in severe cases can cause complete crop failure. However, multiple herbicide resistant P. minor can be controlled by alternative pre-emergence herbicides such as pyroxasulfone, pendimethalin, flumioxazin, trifluralin and flufenacet. Since sole reliance on herbicides is not sustainable in long term basis so there is need to synthesize integrated weed management strategies based on in-depth biological and ecological studies of P. minor. The long-term strategies of efficient weed management and sustainable wheat production should include the use of alternative herbicides, herbicide mixture, along with cultural practicesas crop rotation, competitive varieties, early sowing, weed seed harvesting, previous crop residue mulching andconservation tillage.The integration of various non-chemical weed control options will provide the competitive advantages to the wheat crop over P. minor, at the same time increasing the profitability of the farmer by controlling the weed effectively and reducing the selection pressure for evolution resistance or further extension of herbicide resistance.